2017
DOI: 10.1186/s13287-017-0690-3
|View full text |Cite
|
Sign up to set email alerts
|

Combined platelet-rich plasma and lipofilling treatment provides great improvement in facial skin-induced lesion regeneration for scleroderma patients

Abstract: BackgroundThe use of stem cells, including mesenchymal stem cells (MSCs), for regenerative medicine is gaining interest for the clinical benefits so far obtained in patients. This study investigates the use of adipose autologous tissue in combination with platelet-rich plasma (PRP) to improve the clinical outcome of patients affected by systemic sclerosis (SSc).MethodsAdipose-derived mesenchymal stem cells (AD-MSCs) and PRPs were purified from healthy donors and SSc patients. The multilineage differentiation p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
41
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 44 publications
(45 reference statements)
2
41
0
Order By: Relevance
“…Combinations of distinct regeneration therapies have been vigorously studied in musculoskeletal disorders [34][35][36][37][38]. Dr.…”
Section: Discussionmentioning
confidence: 99%
“…Combinations of distinct regeneration therapies have been vigorously studied in musculoskeletal disorders [34][35][36][37][38]. Dr.…”
Section: Discussionmentioning
confidence: 99%
“…There have been several clinical studies that have shown a beneficial effect of PRP on the outcome of fat graft contouring procedures, skin rejuvenation and chronic connective tissue disorders . There have also been three‐small clinical studies that have shown a beneficial effect on wound healing .…”
Section: The Role Of Prp In Fat Graft Survivalmentioning
confidence: 99%
“…There have been several clinical studies that have shown a beneficial effect of PRP on the outcome of fat graft contouring procedures, 65-69 skin rejuvenation 70 and chronic connective tissue disorders. 71 There have also been three-small clinical studies that have shown a beneficial effect on wound healing. 40,72,73 Although these clinical benefits have suggested improved patient satisfaction, 74 the scientific evidence for the mechanistic relationship between fat and PRP is limited.…”
Section: The Role Of Prp In Fat Graft Survivalmentioning
confidence: 99%
“…In this regard, I believe that some additional cues are worth considering. First, another study has previously analysed the ADSVF from patients with diffuse cutaneous SSc and reported somehow different results 5. In fact, Virzì et al 5 have shown that SSc-ADSVF displays an altered cell composition characterised by a reduced number of cells with a stem-like phenotype, as well as a high content of proinflammatory cytokines and a shortage of angiogenic factors.…”
mentioning
confidence: 99%
“…First, another study has previously analysed the ADSVF from patients with diffuse cutaneous SSc and reported somehow different results 5. In fact, Virzì et al 5 have shown that SSc-ADSVF displays an altered cell composition characterised by a reduced number of cells with a stem-like phenotype, as well as a high content of proinflammatory cytokines and a shortage of angiogenic factors. Moreover, at variance with an earlier study showing that isolated SSc-ADSC exhibit similar biological properties (ie, surface antigenic profile, proliferation and differentiation potentials, immunosuppressive properties and capacity to support endothelial cell tube formation) compared with HD-ADSC,6 Virzì et al 5 found that SSc-ADSC may retain high multipotency but fail to sustain terminally differentiated adipocyte, osteocyte and chondrocyte progenies.…”
mentioning
confidence: 99%